Analisis Efektifitas Laporan Keuangan Melalui Aplikasi SIMDA Di Sekolah Menengah Atas Kota Samarinda Kalimantan Timur - Bambang Supriyanto; Dian Hidayati; Yanto Yanto; Iis Asiska (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
This study uses a descriptive qualitative type of research and data collection used by researchers is to conduct in-depth interviews. The results of this study indicate that the application of the SIMDA Finance application is very helpful in achieving the target to generate finance quickly, and accurately. So that the success of implementing a program can be seen from the point of achieving the goals obtained by paying attention to the outputs generated from the program. So that it can facilitate the management of education costs and then used and allocated according to the needs and activities of the school. Keywords: Effectiveness, Financial Reports, SIMDA Application